Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.0737-1209.2004.21410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Motivation, Health Behaviors, and Functional Status Among Elders in Residential Homes in Korea

Abstract: This study compared the changes in health behaviors, motivation, and functional status between motivation enhancement exercise-program participants and program dropouts over 6 months. A total of 73 older adults living in residential homes participated in the study. Face-to-face interviews were conducted at pretest and then at 10 weeks and 6 months in the program. The participants exercised using traditional Korean dance movements for 50 min, 4 times per week, for 6 months. The subjects were classified as parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 32 publications
(54 reference statements)
5
49
0
4
Order By: Relevance
“…Nine of the 15 training studies were categorized as being Level II (Eyigor et al, 2009;Federici et al, 2005;Hackney et al, 2007;Holmerová et al, personal communication;Hopkins et al, 1990;McKinley et al, 2008;Shigematsu et al, 2002;Sofianidis et al, 2009;Young, Weeks, & Beck, 2007), with the other six training studies being Level III-V (Engels et al, 1998;Jeon et al, 2005;Jeon et al, 2000;Kim et al, 2003;Kudlacek et al, 1997;Song et al, 2004). All three cross-sectional studies were categorized as being Level IV (Uusi-Rasi et al, 1999;Verghese, 2006;Zhang, Ishikawa-Takata, Yamazaki, Morita, & Ohta, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the 15 training studies were categorized as being Level II (Eyigor et al, 2009;Federici et al, 2005;Hackney et al, 2007;Holmerová et al, personal communication;Hopkins et al, 1990;McKinley et al, 2008;Shigematsu et al, 2002;Sofianidis et al, 2009;Young, Weeks, & Beck, 2007), with the other six training studies being Level III-V (Engels et al, 1998;Jeon et al, 2005;Jeon et al, 2000;Kim et al, 2003;Kudlacek et al, 1997;Song et al, 2004). All three cross-sectional studies were categorized as being Level IV (Uusi-Rasi et al, 1999;Verghese, 2006;Zhang, Ishikawa-Takata, Yamazaki, Morita, & Ohta, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Across these 18 studies, a variety of dance forms and outcome measures were used. Of the 15 training studies, the most common forms of dance were traditional Korean (Jeon et al, 2005;Jeon et al, 2000;Kim et al;Song et al) and aerobic (Engels et al; Hopkins et al; Shigematsu et al) dance. Aerobic power, muscle endurance and strength, and static and dynamic balance were the most commonly assessed outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Another study which included 111 older adults who participated in 23 sessions of dance over 12 weeks improved in mobility and general health (measured by the SF-36) and believed their health status was improved by the intervention. 34 In a study of Korean dance for older adults, 35 improvements were found in social interaction components of HRQOL. Likewise, in a qualitative study conducted in Brazil, 60 participants in a ballroom dancing intervention that met for 1 hour, twice weekly for 1 year, reported dancing gave them opportunity to socialize and increase their connection to their own culture.…”
Section: Do Dance and Exercise Affect Hrqol?mentioning
confidence: 99%
“…Increased gait speed following dance/movement therapy was noted in a cohort of people with PD (Westbrook & McKibben, 1989). Older adults who danced were more motivated to 4 pursue healthy, exercise-related behaviors and demonstrated improved balance and functional mobility (Eyigor et al 2007, Song et al 2004. Dance may effectively address motor impairments brought on by aging and illness as dance requires dynamic balance and adaptability to changing environments.…”
Section: Physical Effects Of Dancementioning
confidence: 99%